2009
DOI: 10.1177/0143034309106496
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Teacher Burnout by Increasing Student Engagement

Abstract: Teacher burnout has long been understood to have significant negative effects on teaching efficacy. Research has indicated that student misbehaviour, often a result of disengagement, is a major predictor of teacher burnout. In part to address student disengagement, Hampshire County in England has undertaken a whole-school rights-based reform initiative called Rights, Respect and Responsibility (RRR). This study was designed to examine the effects of RRR on student engagement and teacher burnout over a three-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 14 publications
3
45
1
5
Order By: Relevance
“…Several studies highlight the importance of students' rights and the need for their promotion (Covell & Howe, 2001;Covell et al, 2009). The relationship between students' engagement in school and students' rights is an issue that requires further research (Veiga et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies highlight the importance of students' rights and the need for their promotion (Covell & Howe, 2001;Covell et al, 2009). The relationship between students' engagement in school and students' rights is an issue that requires further research (Veiga et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The literature suggests a relationship between students' rights and their intrinsic motivation and engagement in school (Covell, McNeil, & Howe, 2009). Covell and Howe (2001) claim the existence of a correlation between awareness of rights and self-esteem, which may be related to school variables such as attitudes towards school and students' engagement in school (Veiga, 1996;Veiga, Galvão, Festas, & Taveira, 2012;Woolfolk, 2014).…”
Section: Students' Perceived Rights In the Family And School Contextsmentioning
confidence: 99%
“…Research also has found that when children are educated about their rights in rights-respecting schools, they are more likely to be engaged in school and thus more likely to do better at school (Covell 2010;Covell, McNeil, and Howe 2009). A reason for their greater engagement is that when children receive and understand the message that they have basic rights in schools that model and respect those rightsespecially their right to participation -they are more likely to feel empowered, develop a sense of their own inherent value, and see school as a positive welcoming place (Covell 2010;Howe and Covell 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The details of the programme and its implementation are provided elsewhere . Over a five-year period (2004)(2005)(2006)(2007)(2008), schools in which the RRR was fully implemented have shown improvements in children's school engagement, school climate, citizenship values and behaviours, and peer and teacher relationships, and decreases in anti-social behaviour, bullying, and teacher burnout Covell et al , 2009. Of the 16 primary-level schools on which the five years of data have been collected, the most notable changes have been seen in a school referred to here as School 1.…”
mentioning
confidence: 99%
“…When teachers feel emotionally exhausted and depersonalized, it does not make any difference that what their degree is. Covell, MCNeil, and Howe (2009) asserted that the boring and disruptive environment with forcing too much pressure on the part of teachers can cause burnout even in higher educated teachers. But this is not the case in informal settings.…”
Section: Discussionmentioning
confidence: 99%